Rapid Communication: Postmortem lesions and heart weights of in-transit-loss market pigs in Ontario. Issue 12 (1st December 2017) - Zurbrigg, K.; van Dreumel, T.; Rothschild, M. F.; Alves, D.; Friendship, R.; O'Sullivan, T. L.
ABSTRACT: In-transit losses (ITL) of market-weight pigs are defined as pigs that die or pigs that become nonambulatory during loading and shipping from the farm to the abattoir. The low proportion of ITL in market pigs implies that individual pig factors may influence ITL, in addition to commonly considered environmental or transport factors. Postmortem examinations of in-transit-loss pigs ( n = 85) from 1 Ontario, Canada, abattoir indicated the cause of death to be acute heart failure as a result of cardiac lesions that developed prior to transport. The presence of preexisting cardiac lesions may explain why no or only a few pigs die in a trailer even when the entire load is exposed to extreme temperatures and other common transport risk factors.